The Adoption of Korean Slang on X by Indonesian Students: A Social Identity Approach - Djohar, Jessica Adellene Djohar (Jogjakarta Communication Conference (JCC), 2025)
Social media has become an essential platform for cultural exchange, allowing Indonesians to engage deeply on a global scale. This study examines how the exposure to Korean culture (K-Culture) on X influences the adoption of Korean slang among Swiss German University students. Using Henri Tajfel’s Social Identity Theory as a foundation, the research explores whether adopting common Korean terms reflects a sense of belonging and affects perceptions of national identity. This qualitative study collects data through direct interviews and observations with university students who interact with Korean culture content on X. Findings suggest that while some students experience a subtle shift or blending in cultural self-identification, others maintain a strong attachment to their Indonesian identity. Many view their use of Korean slang as a way to express admiration for Korean culture and connect with global communities, rather than a rejection of their Indonesian roots. This highlights the role of social media in shaping linguistic behaviour and cultural influence, contributing to wider discussions on digital identity and language adaptation in Indonesia.